2022
DOI: 10.1021/acsnano.2c02711
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Synthesis of 2D Verbeekite: Monoclinic PdSe2 Crystals with High Mobility and In-Plane Optical and Electrical Anisotropy

Abstract: PdSe2 has a layered structure with an unusual, puckered Cairo pentagonal tiling. Its atomic bond configuration features planar 4-fold-coordinated Pd atoms and intralayer Se–Se bonds that enable polymorphic phases with distinct electronic and quantum properties, especially when atomically thin. PdSe2 is conventionally orthorhombic, and direct synthesis of its metastable polymorphic phases is still a challenge. Here, we report an ambient-pressure chemical vapor deposition approach to synthesize metastable monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…In addition, it is observed that the I D values increase with temperature in both devices, demonstrating the semiconducting (or insulating) behavior of PdSe 2 . Such insulating behavior was also recently reported by Gu et al in monoclinic PdSe 2 crystals due to the presence of defect-induced localized states . However, their research was conducted on the Si/SiO 2 substrates with a high density of unwanted traps or defects that interfere with the transport behavior of PdSe 2 itself.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In addition, it is observed that the I D values increase with temperature in both devices, demonstrating the semiconducting (or insulating) behavior of PdSe 2 . Such insulating behavior was also recently reported by Gu et al in monoclinic PdSe 2 crystals due to the presence of defect-induced localized states . However, their research was conducted on the Si/SiO 2 substrates with a high density of unwanted traps or defects that interfere with the transport behavior of PdSe 2 itself.…”
Section: Resultssupporting
confidence: 66%
“…Such insulating behavior was also recently reported by Gu et al in monoclinic PdSe 2 crystals due to the presence of defect-induced localized states. 16 However, their research was conducted on the Si/SiO 2 substrates with a high density of unwanted traps or defects that interfere with the transport behavior of PdSe 2 itself. In contrast, our PdSe 2 FET devices were fabricated on h-BN surfaces for maximum screening out of the defective interference from external factors, including substrates, which allows us to focus on the impact of the intrinsic defects of PdSe 2 on its transport behaviors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclinic‐PdSe 2 was found to have a very high electron mobility anisotropy of 1.9, which is higher than orthorhombic‐ PdSe 2 and BP. [ 311 ] It is suggested that metastable phases of typical 2D materials can hold unique properties. Notably, this method is expected to be used in direct synthesis of metastable phases of other 2D van der Waals materials due to its versatility.…”
Section: Perspectivesmentioning
confidence: 99%
“…Recently, an ambient-pressure chemical vapor deposition method was proposed to directly prepare monoclinic-PdSe 2 single crystals on substrates. [311] PdSe 2 has proven to be promising broadband optical modulator and as SAs in ultrafast lasers in the visible and nearinfrared bands. [277,312] However, its metastable phases have scarcely been applied to ultrafast photonic.…”
Section: Perspectivesmentioning
confidence: 99%